Marine protected areas in a changing ocean: Adaptive management can mitigate the synergistic effects of local and climate change impacts. (June 2023) - Zentner, Yanis; Rovira, Graciel·la; Margarit, Núria; Ortega, Júlia; Casals, David; Medrano, Alba; Pagès-Escolà, Marta; Aspillaga, Eneko; Capdevila, Pol; Figuerola-Ferrando, Laura; Riera, Joan Lluís; Hereu, Bernat; et al.
Abstract: During the last two decades, several Marine Heatwaves (MHWs) have affected coralligenous assemblages in the Mediterranean Sea, causing catastrophic mass mortalities of several habitat-forming species such as gorgonians, corals, and sponges. Even though Marine Protected Areas (MPAs) are contributing to effectively protect marine ecosystems, the impacts associated to extreme climatic events within MPAs are jeopardizing their protective role. Therefore, minimizing local stressors within MPAs is crucial to minimize interactive effects with global, more difficult to manage, stressors. To address this, we assessed to what extent the regulation of diving frequentation can support more effective protection to climate change, focusing on the case study of the Medes Islands, which has recently suffered the impacts of different global stressors and is one of the most visited MPAs in the Mediterranean Sea. We combined 6 years of demographic data of the red gorgonian Paramuricea clavata with population modelling tools, to explore the long-term viability of this species to different managing schemes and mass mortality events scenarios. Overall, our results show that climate-adaptive management of the recreational diving activity under climate change can enhance the long-term viability of this key Mediterranean habitat-forming octocoral, which is otherwise predicted to go locally extinct at shallow depths (<25 m) within the next 20 years. This study provides one of the few attempts to quantify to what extent an adaptive management scheme may help delay climate change impacts in a Marine Protected Area. Highlights: Marine heatwaves are severely impacting key Mediterranean octocorals. Over-frequentation by divers can be detrimental in no-take marine protected areas. Interactions between local and global stressors can be synergistic. Adaptive management on local impacts gives borrowed time to face climate change. Long-term monitoring and modelling are key to design adaptive management schemes.